Experimental and clinical study of the efficacy of medicines containing omega-3 and 6 polyunsaturated fatty acids, in the treatment of inflammatory skin diseases - Svetlana V. Grebennikova; Yuriy S. Maklyakov (Belgorod National Research University, 2018)
Introduction: Over the recent years, the attention of scientists regarding the search for alternative means of treatment, including local therapy, of inflammatory skin diseases, has been focused in recent years on medicines containing omega-3 and 6 polyunsaturated fatty acids (PUFA). Objectives: to substantiate the feasibility of using medicines containing omega-3 and 6 polyunsaturated fatty acids and antioxidants in the treatment of inflammatory skin diseases. Methods:The studies were carried out on 224 conventional white rats of the Wistar line in compliance with the international principles of the European Convention for the Protection of Vertebrates. A burn injury was used to cause experimental simple irritant contact dermatitis. After trying various treatment options with using Omegaven, histopathological examinations of 18 fragments of affected skin of white rats with cross sections stained with hematoxylin-eosin and pikrofuxin by Van Gieson's method. The state of lipid peroxidation (LPO) in blood and affected skin was evaluated in the animals. One hundred forty-six patients with inflammatory skin diseases (dermatitis simple irritant contact, allergic contact dermatitis, atopic dermatitis, neurodermatitis, psoriasis, cutaneous mastocytosis in children) were observed. In treatment, there were used medicines with omega-3 and 6 PUFA or an antioxidant medicines. Results and discussion: Skin reactions of dermatitis simple irritant contact in rats after burn injury were evaluated at different points of time. The observations showed higher efficacy of medicines containing PUFA than standard anti-inflammatory agents in the treatment of simple irritant contact dermatitis. Histopathological examination of the skin of white rats with simple irritant contact dermatitis after the 11-day treatment revealed that the expression and composition of the cellular reaction in the lesions with a predominating lymphocytes and macrophages (mainly cell response) differ significantly from those trated with Radevit ointment (segmented neutrophil leukocytes, eosinophils - delay in the acute phase of inflammation). There was identified a smaller thickness (up to 1/3) of the strips of granulation tissue under the actively proliferating cells of the epidermis. It was possible to demonstrate the superiority with respect to reducing the activity of LPO medicines containing omega-3 and 6 PUFA, over those with anti-inflammatory action. The clinical observations of patients showed high efficacy of the local treatment with medicines containing omega-3 and 6 PUFA, or antioxidant. Conclusion: For the first time, the mechanism of implementing an anti-inflammatory effect of the experimental medicines containing omega-3 and 6 polyunsaturated fatty acids (Omegaven, Vitamin F99 cream rich), - an antioxidant effect - when treating simple irritant contact dermatitis when treating simple irritant contact dermatitis; that is the weakening of the severity of oxidative stress. For the first time, the greatest contribution of an increased activity of catalase to the weakening of oxidative stress in the affected skin is shown.